Bernanke/Blinder revisited - The New Keynesian model with credit channel - Sven Offick; Hans-Werner Wohltmann (Kiel University, Department of Economics, 2014)
This paper integrates a money and credit market into a static approximation of the baseline New Keynesian model based on a money-and-credit-in-the-utility approach, in which real balances and borrowing contribute to the household's utility. In this framework, the central bank has no direct control over the interest rate on bonds. Instead, the central bank's instrument variables are the monetary base and the refinancing rate, i.e. the rate at which the central bank provides loans to the banking sector. Our approach gives rise to a credit channel, in which current and expected future interest rates on the bond and loan market directly affect current goods demand. The credit channel amplifies the output effects of isolated monetary disturbances. Taking changes in private (inflation and interest rate) expectations into account, we find that - contrarily to Bernanke and Blinder (1988) - the credit channel may also dampen the output effects of monetary disturbances.
Keywords: A20; E51; E52; 330; Money; Loan; Money-and-credit-in-the-utility; Credit channel; New Keynesian model; Monetary policy